Quality assessment reporting checklists for microsimulation models: A scoping review protocol - Claire de Oliveira (PLoS ONE, 2026)
Background Microsimulation models are computer-based models that can be used to understand how economic agents behave in different situations. These models are used by governments to help them make decisions. However, it is important these models are well built and produce useful information. Reporting checklists can help guide researchers confirm that all the necessary elements are included in a model. There are currently no formal reporting checklists to evaluate the quality of microsimulation models. This protocol aims to describe a scoping review, which will retrieve and synthesise the literature on any existing quality assessment checklists for microsimulation models and/or any literature that provides best practices, guidelines, and/or recommendations around which elements should be included. Methods We will undertake a scoping review followed the PRISMA guidelines for Scoping Reviews. We will search MEDLINE, Embase, EconLit, and Web of Science, with an update closer to the time of manuscript submission. In addition, where relevant, we will undertake Google searches and searches on specific journals (e.g., International Journal of Microsimulation) and websites (e.g., https://www.microsimulation.ac.uk/ ) to complement the database searches. We will extract relevant data on quality dimensions and use a narrative synthesis to describe the recommendations. Discussion There are no formal checklists to assess the quality of microsimulation models. Moreover, no scoping reviews have been undertaken on this topic. This work will synthesise any existing recommendations regarding the development of robust microsimulation models. A validated quality assessment reporting checklist will be the first of its kind and thus, fill an important gap in the literature.